2015
DOI: 10.1038/leu.2015.325
|View full text |Cite
|
Sign up to set email alerts
|

Functional inhibition of mesenchymal stromal cells in acute myeloid leukemia

Abstract: Hematopoietic insufficiency is the hallmark of acute myeloid leukemia (AML) and predisposes patients to life-threatening complications such as bleeding and infections. Addressing the contribution of mesenchymal stromal cells (MSC) to AML-induced hematopoietic failure we show that MSC from AML patients (n = 64) exhibit significant growth deficiency and impaired osteogenic differentiation capacity. This was molecularly reflected by a specific methylation signature affecting pathways involved in cell differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
176
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(192 citation statements)
references
References 38 publications
13
176
1
2
Order By: Relevance
“…Along with impaired stromal support of healthy HSPC this suggests that MSC alterations contribute substantially to the inadequate hematopoiesis in MDS and AML. 12,13 Furthermore, these findings imply significantly deregulated bi-directional crosstalk between malignant myeloid cells and MSC. In the current analysis, we used discovery-based strategies, such as RNA sequencing, followed by candidate-testing approaches.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Along with impaired stromal support of healthy HSPC this suggests that MSC alterations contribute substantially to the inadequate hematopoiesis in MDS and AML. 12,13 Furthermore, these findings imply significantly deregulated bi-directional crosstalk between malignant myeloid cells and MSC. In the current analysis, we used discovery-based strategies, such as RNA sequencing, followed by candidate-testing approaches.…”
Section: Introductionmentioning
confidence: 90%
“…12,13 All experiments were carried out using MSC derived from passages 3–4. Furthermore, CD34 + HSPC were obtained from the bone marrow of healthy controls by density gradient separation and subsequent immunomagnetic selection (Miltenyi Biotec, Bergisch Gladbach, Germany) as described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that mesenchymal stromal cells from patients with MDS and AML are aberrantly methylated [60][61][62]. Along with this, Verma et al showed that Aza might mediate at least some of its efficacy via demethylation of the BM stroma [3].…”
Section: Mode Of Actionmentioning
confidence: 99%
“…15 This might enhance the LSCs quiescence, leading to chemotherapy resistance. 1,[16][17][18][19] A recent study reported that the inhibition of SIRPα signalling in macrophages impairs engraftment of human LSCs in immunocompromised NSG mice. 20 Clinically, the accumulation of TAMs in the lymph nodes of patients with classic Hodgkin lymphoma was associated with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%